ANALISIS UNSUR INTRINSIK NOVEL MENGGAPAI MATAHARI KARYA DERMAWAN WIBISONO - Andi Permana; Lia Juwita; Ai Siti Zenab (IKIP Siliwangi, 2019)
Writing of literature will be more interesting when combined with intrinsic elements that can attract the interest of readers in various circles, be it children, teenagers, adults, and parents. Analysis of this novel aims to describe the intrinsic elements contained in the novel Menggapai Matahari by Dermawan Wibisono. The data source used in this research is the novel Menggapai Matahari by Dermawan Wibisono. The method used is qualitative descriptive method. The results of this study indicate that the novel Menggapai Matahari by Dermawan Wibisono there is a theme that is a child trying to restore the confidence of his mother, a pareatif figure, using a forward flow, with the background place, time and atmosphere. The point of view that is used is the first person the main actor and there is a mandate to keep the parents brightening and the mandate contained in the novel Reach the Sun by Dermawan Wibisono is to always distrust to anyone except to God.